In-Company Foreign Language Training: A Teacher’s Perspective - Dorota Lipińska (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
Teaching languages in a company environment is a relatively new phenomenon which has appeared as a result of competition on a job market. Nowadays companies offer various fringe benefits to their best employees, free language courses among them. This is a completely new situation for language teachers who are faced with a challenge of working in a new environment, not resembling schools, universities or language schools. They need to adapt to new requirements and deal with new problems and difficulties they were not prepared or trained for (Scrivener, 2011; Chong, 2013). The aim of this paper is to check what kind of difficulties and problems arise while teaching an L2 in a company. A group of L2/foreign language (English, German and French) teachers filled in an anonymous questionnaire concerning their work environment. The subjects came from various areas of Poland. The obtained information was divided into thematic sections and showed that the scope of perceived difficulties is really vast. It suggests that the topic should be analysed and studied further and corporate teaching ought to be formally taught as a part of a teacher training programme.